1987
DOI: 10.1002/ijc.2910400105
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological analysis of lymphocyte subpopulations infiltrating breast carcinomas and benign lesions

Abstract: We characterized different subpopulations of infiltrating mononuclear cells using 8 monoclonal antibodies (MAbs) on serial cryosections of breast tissue from 85 cancer patients and 32 samples of benign lesions, and the ABC technique. In general, lymphocytes were found more frequently and more abundantly in cancerous lesions. The infiltrates consisted mainly of T-cells in close contact with malignant cell-nests. T-helper/inducer cells clearly predominated over T-suppressor/cytotoxic cells in neoplastic tissues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Immunohistochemistry showed that the diffuse inflammation in tumours was predominantly composed of T cells and macrophages. The majority of other studies have found that T cells outnumbered macrophages Bhan and DesMarais, 1983;Giorno, 1983;Hurliman et al, 1985; Kleist, 1987;Zuk and Walker, 1987), but a significant minority, like us, found more macrophages than T cells (Gottlinger et al, 1985;Horny et al, 1986;van Ravenswaay et al, 1992). Few B cells and few or no natural killer cells are consistent findings in the literature.…”
Section: Discussionmentioning
confidence: 42%
“…Immunohistochemistry showed that the diffuse inflammation in tumours was predominantly composed of T cells and macrophages. The majority of other studies have found that T cells outnumbered macrophages Bhan and DesMarais, 1983;Giorno, 1983;Hurliman et al, 1985; Kleist, 1987;Zuk and Walker, 1987), but a significant minority, like us, found more macrophages than T cells (Gottlinger et al, 1985;Horny et al, 1986;van Ravenswaay et al, 1992). Few B cells and few or no natural killer cells are consistent findings in the literature.…”
Section: Discussionmentioning
confidence: 42%
“…Since that time there have been numerojis additional conflicting rerports of associations between infiltration and for example favourable prognosis (Black et al, 1975;Dawson et al, 1982;Stenkvist et al, 1982), and poor prognosis (Roses et al, 1982;Fisher et al, 1983). However, a consistent theme in more recent studies has been the association of lymphoplasmacytic infiltration and histological features of poor prognosis such as poor grade, nuclear pleomorphism, tumour necrosis and lymph node invasion by tumour (Black et al, 1975;Lauder et al, 1977;Fisher et al, 1983;von Kleist et al, 1987;Zuk & Walker, 1987 Schoorl et al, 1976;Hsu et al, 1981;Hurlimann & Soraga, 1985;Lwin et al, 1985;von Kleist et al, 1987;Zuk & Walker, 1987 (1985) report that B cells can represent up to 48% of the total number of T cells, whilst Zuk and Walker (1987) provide evidence that the proportion of B cells increase relative to T cells in carcinoma as opposed to benign breast, with an overall B:T cell ratio as high as 1:2.…”
Section: Discussionmentioning
confidence: 84%
“…Figure 1 shows the distribution of patients relative to 22 Meecham/Char/Kaleta-Michaels Infiltrating Lymphocytes CD4 (helper/inducer) + CD8 (cytotoxic/suppressor) + the degree of lymphocyte infiltration. Ten pa tients (23.9%) had intratumor T cell infil trates that comprised more than 5% of the tumor.…”
Section: Cell Phenotypes In Uveal Melanomamentioning
confidence: 99%